2011
DOI: 10.1155/2011/804583
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Feature of Men Who Benefit from Dose Escalation of Naftopidil for Lower Urinary Tract Symptoms: A Prospective Study

Abstract: Objectives. To examine the feature of men who benefit from dose escalation of naftopidil for lower urinary tract symptoms (LUTSs). Methods. Based on the IPSS, men reporting LUTS were prospectively studied using 50 mg/day of naftopidil for the first 4 weeks; satisfied patients continued its 50 mg/day (n = 11), and those reporting unsatisfactory improvement received its 75 mg/day (n = 35) for the next 4 weeks. Results. The 75 mg group showed improvement in the total IPSS and QOL score in a dose-dependent manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…13 Mizusawa et al reported that 4-week treatment with 50 mg/day of naftopidil was effective in 23.9% of the patients when the patients' satisfaction with their QoL of urinary conditions was defined as effective. 14 We evaluated the efficacy of 8-week treatment with 50 mg/ day of naftopidil based on the IPSS-QoL at the eighth week. The difference in the results between the previous and present studies might be attributable to the different treatment period and the different evaluation method for efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Mizusawa et al reported that 4-week treatment with 50 mg/day of naftopidil was effective in 23.9% of the patients when the patients' satisfaction with their QoL of urinary conditions was defined as effective. 14 We evaluated the efficacy of 8-week treatment with 50 mg/ day of naftopidil based on the IPSS-QoL at the eighth week. The difference in the results between the previous and present studies might be attributable to the different treatment period and the different evaluation method for efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although naftopidil is usually administered at 50 mg/day, 7,10 the efficacy of 75 mg/day administration has been recently reported. [11][12][13][14] 50 mg/day based on the IPSS-QoL index, the dosage was maintained at 50 mg/day in the responders, but was increased to 75 mg/day in the poor responders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mizusawa and colleagues prospectively studied patients' preference/satisfaction with 50 mg/day compared with 75 mg/day of naftopidil, and analyzed differences in their background [Mizusawa et al 2011]. Patients reporting unsatisfactory improvement in LUTS with 50 mg/day of naftopidil for 4 weeks based on a question 'are you satisfied with your current urinary state, yes or no?'…”
Section: After Approval Of Naftopidil For the Management Of Benign Prmentioning
confidence: 99%
“…Several investigators, including our group, have carried out similar clinical studies to evaluate the efficacy of increasing the naftopidil dose to 75 mg/day in cases in which a dose of 50 mg/day was ineffective, and suggested that the optimal dose of naftopidil is 75 mg/day in some patients. In our study, there was no significant difference in the prostate volume between responders and non‐responders to naftopidil 50 mg/day.…”
mentioning
confidence: 99%